Stabilitas Lereng dengan Kombinasi Dinding Penahan Tanah (DPT) dan Tiang Pancang Berdasarkan Variasi Kedalaman Tiang - Arissa Sabilla; Shafira Salsabila; Rajib Muammar; Ari Juanda; Rauzah Munauwarah (Yayasan Literasi Sains Indonesia, 2026)
Slope stability is an important aspect in construction planning, especially in areas with weak soil conditions and high rainfall that have the potential to trigger landslides. This study aims to analyze the effect of variations in pile depth in combination with retaining walls (DPT) on increasing slope stability. The method used is numerical analysis using Plaxis software with a Mohr-Coulomb soil model based on secondary data of geotechnical parameters. The variations in pile depth described include 12 meters, 16 meters, 19 meters, and 20 meters. The results of the analysis show that the existing slope condition has a safety factor (SF) value of 1.270 and decreases to 1.064 after being given additional loads, which indicates unstable conditions. The application of DPT and pile reinforcement can significantly increase the SF value, with values ​​of 1.540 (12 m), 1.124 (16 m), 2.354 (19 m), and 2.450 (20 m), respectively. A depth of 19 meters is determined as the optimal condition because it provides a significant and efficient increase in stability. Thus, variations in pile depth have been shown to significantly impact slope stability and can be used as a reference in designing safe and economical slope reinforcement.